Designing an efficient SMI process : A case study in the battery industry - Kummunmäki, Antti (My University, 2022)
This study has been conducted as an assignment for a Finnish battery industry operator, Valmet Automotive EV Power Oy. Supply market intelligence (SMI) is a fundamental part of companies' competitiveness. Numerous current trends, such as the pursuit of more sustainable operations throughout the supplier network, the increase in open innovation and the more strategic position of procurement in general, further emphasize the importance of SMI. Without market intelligence, there is a risk of having to make significant decisions as if blindfolded. Whereas the customer and competitor markets have been actively and systematically mapped for decades, the supply market has received less attention. Previous studies highlight the value of SMI from different angles but provide fragmented answers on how supply market intelligence should be approached from a process perspective. Thus, the focus of this research is to address the research gap and the need of the principal company by developing an efficient SMI process that covers all steps from identifying an information need to finally utilizing the information. Efficiency is emphasized, as limited resources are one of the main practical obstacles to SMI operations. The research question (How to manage supply market intelligence systematically and efficiently?) was approached by means of constructive research, combining theory and empiricism. First, a purely theoretical process prototype was created as a result of a literature review. The prototype was then tested, and its shortcomings were empirically identified and solved through interviews, expert meetings and workshops. The participants group comprised of the case company’s employees and academic experts. The final process consists of four main phases: planning, collection, sharing, and use of SMI. These main phases, in turn, are divided into fourteen concrete steps with recommendations for action. The steps are supported by several practical tools developed during the study. In addition, thirteen efficiency principles and a large number of other findings related to supply market intelligence were identified during the study which provide a good basis for both the design of a new SMI process and the refinement of an old one. The main conclusion drawn from this study is that it is possible to bring efficiency and systematicity to SMI activities through process development. By balancing between concreteness and genericity, a diverse spectrum of SMI needs can be treated coherently within a single process. The process itself provides an extensive and visual framework for both the literature and the practitioners to reflect on and develop SMI operations. At the same time, the research recommends various potential research areas around the process. For the principal company, the study provides an answer to the prevailing situation, considering their context.

Tämä tutkimus on tehty toimeksiantona suomalaiselle akkuteollisuuden toimijalle, Valmet Automotive EV Power Oy:lle. Toimittajamarkkinatuntemus (SMI) on keskeinen osa yritysten kilpailukykyä. Lukuisat vallitsevat trendit kuten pyrkimys kestävämpään toimintaan koko toimittajaverkoston laajuudella, avoimen innovoinnin lisääntyminen ja hankinnan yleisesti strategisempi asema korostavat SMI:n merkitystä entisestään. Ilman markkinatuntemusta on vaarana joutua tekemään suuria päätöksiä ikään kuin silmät sidottuina. Siinä missä asiakas- ja kilpailijamarkkinaa on aktiivisesti ja systemaattisesti kartoitettu jo vuosikymmenet ovat toimittajamarkkinat jääneet vähemmälle huomiolle. Aiemmat tutkimukset korostavat aiheen merkitystä eri kulmista, mutta tarjoavat hajanaisia vastauksia siihen, kuinka toimittajamarkkinatuntemusta pitäisi kokonaisuutena lähestyä. Täten tässä tutkimuksessa vastattiin tutkimusaukkoon ja toimeksiantajan tarpeeseen kehittämällä tehokas SMI-prosessi, joka kattaa kaikki vaiheet tietotarpeen tunnistamisesta tiedon hyödyntämiseen saakka. Tehokkuutta painotettiin, sillä resurssien rajallisuus muodostaa yhden keskeisimmistä käytännön esteistä SMI-toiminnalle. Tutkimuskysymystä (Kuinka hallita toimittajamarkkinatuntemusta tehokkaasti ja systemaattisesti?) lähestyttiin konstruktiivisen tutkimuksen keinoin yhdistelemällä teoriaa ja empiriaa. Ensin kirjallisuuskatsauksen tuloksena luotiin puhtaasti teoreettinen prosessiprototyyppi. Sen jälkeen prototyyppiä testattiin ja sen puutteita ratkottiin empiirisesti haastatteluiden, asiantuntijatapaamisten ja työpajojen avulla. Osallistujajoukko koostui toimeksiantajan työntekijöistä ja aiheeseen vihkiytyneistä tutkijoista. Lopullinen prosessi koostuu neljästä päävaiheesta: suunnittelu, kerääminen, jakaminen ja hyödyntäminen. Päävaiheet puolestaan jakautuvat 14 konkreettiseen alavaiheeseen toimintasuosituksineen. Vaiheita tukevat useat tutkimuksen aikana kehitetyt käytännönläheiset työkalut. Lisäksi tutkimuksessa tunnistettiin 13 tehokkuusprinsiippiä ja suuri joukko muita toimittajamarkkinatuntemukseen liittyviä havaintoja, jotka tarjoavat hyvän pohjan niin uuden SMI prosessin suunnittelemiselle kuin vanhan kehittämiselle. Tutkimuksella osoitettiin, että SMI-toimintaan on mahdollista tuoda tehokkuutta ja systemaattisuutta prosessikehityksen keinoin. Tasapainoilemalla konkreettisuuden ja geneerisyyden välimaastossa, voidaan moninaista SMI-tarpeiden kirjoa käsitellä yhtenäisesti yhden prosessin sisällä. Prosessi itsessään tarjoaa laajan ja visuaalisen viitekehyksen niin kirjallisuudelle kuin käytännön liiketoiminnallekin reflektoida ja kehittää SMI-toimintaa. Samalla tutkimus osoittaa lukuisia uusia tutkimuskohteita prosessin ympäriltä. Toimeksiantajalle tutkimus tarjoaa vastauksen esitettyyn tarpeeseen heidän kontekstinsa huomioiden.
Keywords: SMI, supply market intelligence, process development, battery industry, market intelligence